Heavy metal accumulation in Pelargonium hortorum: effects on growth and development - Orroño, Daniela I. (2009)
Ornamental plants have been proposed for growth in heavy metal (HM) contaminated soils, and also for phytoremediation. We evaluate biomass production and studied HM accumulations in Pelargonium hortorum. Plants were grown for 16 weeks in HM spiked soils with cadmium, chromium, copper, lead nickel and zinc. Treatments were i) control, non-spiked soil, ii) medium concentration treatment and iii) high concentration treatment. Plants were harvested four times and roots, stems, leaves, and flowers were analyzed. The concentrations of HM were determined using ICP. A significant reduction in biomass production was observed in spiked soils compared with the control and different indices confirmed that P. hortorum was affected by HM. Heavy metals concentrations was higher in roots than in aerial organs. Plant uptake rate of HM in roots and aerial biomass showed different pattern for each element. Flowering was highly sensitive to HM soil concentration.